The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/17588359211000591
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dysbiosis-inducing drugs, overall survival and tumor response in patients treated with immune checkpoint inhibitors

Abstract: Background: There are conflicting data on the effects of dysbiosis-inducing drugs, and especially antibiotics (ATBs), on clinical outcomes in patients treated with immune checkpoint inhibitors (ICIs). There is a particular lack of data for patients with melanoma. Methods: We performed a single-center retrospective study of the associations between ATBs and other drugs known to modify the gut microbiota (proton pump inhibitors, nonsteroidal anti-inflammatory drugs, statins, opioids, anti-vitamin K, levothyroxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 63 publications
(146 reference statements)
0
32
0
1
Order By: Relevance
“…reported a significant improvement in clinical response in patients taking metformin plus ICI therapy (ORR = 47.1% with vs . 24.5% without, p = 0.02) but this benefit did not equate to longer OS or PFS ( 40 ). Three studies reported a trend towards improved ICI efficacy with metformin but was not statistically significant ( 8 , 20 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…reported a significant improvement in clinical response in patients taking metformin plus ICI therapy (ORR = 47.1% with vs . 24.5% without, p = 0.02) but this benefit did not equate to longer OS or PFS ( 40 ). Three studies reported a trend towards improved ICI efficacy with metformin but was not statistically significant ( 8 , 20 , 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, these meta-analyses included only five and seven studies. Since then, many studies have continued to explore this DDI, and Table 5 summarizes the latest ones ( Mukherjee et al, 2018 ; Zhao et al, 2019 ; Chalabi et al, 2020 ; Cortellini et al, 2020 ; Hopkins et al, 2020 ; Iglesias-Santamaría, 2020 ; Buti et al, 2021 ; Cortellini et al, 2021 ; Gaucher et al, 2021 ; Jun et al, 2021 ; Rounis et al, 2021 ; Ruiz-Bañobre et al, 2021 ). Robust recommendations for PPI use cannot be inferred given the retrospective nature of the currently available evidence, but caution should be exercised with ICIs ( Rossi et al, 2019 ; Hussain et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that exposure to corticosteroids, antibiotics, and PPI leads to progressively poorer outcomes after ICI therapy. 22 , 23 Conversely, a meta‐analysis that included 1167 patients with cancer examined the effect of PPI on the survival of patients with cancer treated with ICIs; this study showed that the concomitant use of PPI did not significantly affect OS (HR: 0.996; 95% CI [0.486, 1.447]) or PFS (HR: 0.858; 95% CI [0.388, 1.328]). 24 These contentious outcomes stem mainly from the indirect analysis of the effects of dysbiosis‐inducing drugs on oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%